PENGARUH IMPLEMENTASI PENGENDALIAN INTERN, BUDAYA ORGANISASI DAN TOTAL QUALITY MANAGEMENT DALAM PENERAPAN GOOD GOVERNANCE DAN IMPLIKASINYA TERHADAP KINERJA ORGANISASI DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi pada Lembaga Amil Zakat - Sri Fadilah (Indonesian Journal of Economics and Business, 2011)
This study aims to analyze: (1) The effect of implementation of internal controls, implementation of organizational culture and total quality management implementation both partially and simultaneously to the application of good governance, (2) The effect of implementation of internal controls, organizational culture and total quality management both partially and simultaneously to organizational performance and through the implementation of good governance and (3) The effect of application of good governance on the performance of the organization and through consumer confidence.The study uses 50 active-LAZ population targets at Forum Zakat as the active member, while processed data is 41 of target sample of 34. the sampling method used is proportionate stratified sample. The study uses primary and secondary data. An analysis instrument used is structural equation modeling (SEM) with partial least square (PLS). The exogenous variable consists of (1) Internal control implementation; (2) Organization culture implementation; and (3) Organization culture.The results show that in both  partially and simultaneously an implementation of internal control, organization culture, and total quality management influences positively and significantly on the good governance. The simultaneous influence of 54.90% and the remains is of 45.10% described and influenced by unobserved factors. Partially, an influence of internal control is of 24.60%, organization culture of 13%, and total quality management is of 17.30%. The research gives evidence in both partially and simultaneously on implementation of internal control, organization culture, and total quality management to the employee performance and the good governance. Simultaneously, the influence is of 41.60% and the remains about 58.60% influenced by unobserved factors including an implementation of good governance and customer thrust. Partially, an influence of internal control implementation and good governance is of 12.90%, culture organization and good governance is of 18.90%, and total quality management and good governance is of 9.80%. Finally, the study shows that an influence of total implementation to the organization performance by customer trust as the intervening variable is 18.20%. Directly, an implementation of good governance is of 13.80% and indirectly or under customer trust is of 4.40%.